2012
DOI: 10.1155/2012/489428
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E: Essential Catalyst of the Alzheimer Amyloid Cascade

Abstract: The amyloid cascade hypothesis remains a robust model of AD neurodegeneration. However, amyloid deposits contain proteins besides Aβ, such as apolipoprotein E (apoE). Inheritance of the apoE4 allele is the strongest genetic risk factor for late-onset AD. However, there is no consensus on how different apoE isotypes contribute to AD pathogenesis. It has been hypothesized that apoE and apoE4 in particular is an amyloid catalyst or “pathological chaperone”. Alternatively it has been posited that apoE regulates Aβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 84 publications
2
93
0
Order By: Relevance
“…Therefore, pharmacological interventions to reduce synj1 expression levels and/or phosphatase activities could achieve similar functional outcomes in ApoE4 conditions. Several current therapeutic strategies have been focused on removing or ablating ApoE4, based on the observations that ApoE4 contributes to AD-related neurodegenerative processes and that total absence of ApoE proteins has no significant neurocognitive deficits (33,34). However, our data suggest that ApoE is critical to maintain brain phospholipid homeostasis and that ApoE4 exerts less of this effect than other isoforms.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, pharmacological interventions to reduce synj1 expression levels and/or phosphatase activities could achieve similar functional outcomes in ApoE4 conditions. Several current therapeutic strategies have been focused on removing or ablating ApoE4, based on the observations that ApoE4 contributes to AD-related neurodegenerative processes and that total absence of ApoE proteins has no significant neurocognitive deficits (33,34). However, our data suggest that ApoE is critical to maintain brain phospholipid homeostasis and that ApoE4 exerts less of this effect than other isoforms.…”
Section: Discussionmentioning
confidence: 77%
“…Numerous studies have found that ApoE ε4 enhances the aggregation [37] and impairs the clearance [46] of Aβ in the brain. This dual role of ApoE ε4 may be a critical determinant of the synaptic loss and memory impairment that characterizes AD [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Since the early 1990s, several studies have evaluated the association between the apolipoprotein E (ApoE) ε4 allele and AD in various ethnic groups [8-14]. Although the ε4 allele of the ApoE gene has been established in Caucasians as the most important risk factor of nonmonogenic forms of AD in Caucasians, the influence of ApoE ε4 appears to be weaker among Asian populations [10, 14-17].…”
Section: Introductionmentioning
confidence: 99%
“…In DS, elevated numbers of S100β positive astrocytes are present throughout life and are associated with neuritic dystrophy [41]. Other inflammatory molecules, including ApoE and alpha1-antichymotrypsin, have also been shown to be upregulated in astrocytes and microglia in both AD and DS and are found in amyloid plaques [42]. Interestingly, a recent study demonstrated alterations in the transcriptome between a pair of monozygotic twins, where only one twin had DS [43].…”
Section: Pathologic and Mechanistic Links Between Ds And Admentioning
confidence: 99%
“…Because NE signaling has been shown to regulate growth factor expression, inflammatory pathways, and amyloid processing, treatment with NE enhancing drugs may be neuroprotective and prevent or slow further neuropathology progression [76]. Other novel treatment options considered included stimulating innate immune system with a Toll-like receptor 9 ligand [77], inhibiting the interaction of apoE with Aβ, which may prevent or slow oligomerization and polymerization of Aβ, thus halting or reducing the pathogenic cascade [42]. It is unclear at this point whether treatment options for DS individuals will be the same as the general population or possibly require additional treatments in combination.…”
Section: Ad Clinical Trials In Individuals With Dsmentioning
confidence: 99%